2016
DOI: 10.1021/acsami.5b06225
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Support Interactions of Platinum Nanoparticles Decorated N-Doped Carbon Nanofibers for the Oxygen Reduction Reaction

Abstract: N-doped carbon materials are discussed as catalyst supports for the electrochemical oxygen reduction reaction (ORR) in fuel cells. This work deals with the preparation of Pt nanoparticles (NPs) supported on N-doped carbon nanofibers (N-CNF) from a polyaniline nanofiber (PANI NF) precursor, and investigates the ORR activity of the produced materials. Initially, Pt NPs are deposited on PANI NFs. The PANI NF precursors are characterized by near-edge X-ray absorption fine structure (NEXAFS) and transmission electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(94 citation statements)
references
References 48 publications
5
86
0
3
Order By: Relevance
“…From the high‐resolution XPS spectrum of the C 1s (Figure b), C−C, C−N, C−O and C=O bonds are observed. The N 1s spectrum of Pt/N‐OHPC (Figure c) shows five peaks, assigning to pyridinic N (398.2 eV), Pt−N bond (399.0 eV), pyrrolic N (399.8 eV), graphitic N (401.1 eV) and N−O bond (402.5 eV) . It was reported that graphitic N could increase the electronic conductivity of carbon materials and pyridinic and pyrrolic N can increase active sites for ORR, which are both important for electrochemical reaction.…”
Section: Resultssupporting
confidence: 56%
“…From the high‐resolution XPS spectrum of the C 1s (Figure b), C−C, C−N, C−O and C=O bonds are observed. The N 1s spectrum of Pt/N‐OHPC (Figure c) shows five peaks, assigning to pyridinic N (398.2 eV), Pt−N bond (399.0 eV), pyrrolic N (399.8 eV), graphitic N (401.1 eV) and N−O bond (402.5 eV) . It was reported that graphitic N could increase the electronic conductivity of carbon materials and pyridinic and pyrrolic N can increase active sites for ORR, which are both important for electrochemical reaction.…”
Section: Resultssupporting
confidence: 56%
“…Moreover, other peaks can appear due to π* transitions deriving from the introduction of functionalities (e.g., amine or imide groups) [89].…”
Section: X-ray Absorption Spectroscopy (Xas)mentioning
confidence: 99%
“…[6] The most active catalystf or ORR, platinum-based catalysts, cannotb ew idely used on account of their high cost, inferior long-termd urability [7] andl ow tolerance to the intermediate products in fuel cells. [8] Developing cheap, high-activity low- [9] or non-platinum [10] catalysts is the immediate way to solve these problems. In the last decade, heteroatom-doped (N, P, S, B) carbon materials were thought to be ap romising alternative to platinum in the ORR.…”
Section: Introductionmentioning
confidence: 99%